Mettre en évidence un facteur commun, le souligner puis factoriser.

A= 3x - 3

B= 4x +6

C= 8 + 2x

D= 7y² - 5y

E= 30a + 36a²

F= -9x² - 9

2
A= 3(x-1)
B= 2(2x}+ 3) C= 2(4+3) D= y (7y-5) E= 6a (5+6a) F= 9 (-x au carré-1°
F= -x au carré - 1)

Réponses

2013-12-15T15:06:25+01:00
A = 3x-3 = 3(x-1)
B = 4x+6 = 2(2x+3)
C = 8+2x = 2(4+x)
D = 7y²-5y = y(7y-5)
E = 30a-36a = a(30-36a) = 2a(15-18a)
F = -9x²-9 = -9(x²-1)

Meilleure réponse !
2013-12-15T15:09:25+01:00
A=3x-3
A=3(x-1)

B=4x+6
B=2(2x+3)

C=8+2x
C=2(4+x)

D=7y²-5y
D=y(7y-5)

E=30a+36a²
E=6a(5+6a)

F=-9x²-9
F=9(-x²-1)